أثر النفقات العامة على التنمية الاقتصادية في العراق - خلف، قصي عبدالله (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2018)
تهدف الدراسة إلى بيان أثر النفقات العامة على التنمية الاقتصادية في العراق للفترة الزمنية بين (2003- 2015)، ولتحقيق أهداف الدراسة استخدم الباحث المنهج الوصفي التحليلي في بيان الأثر القياسي للنفقات العامة باعتبارها المتغير المستقل على مؤشرات التنمية الاقتصادية للسلسلة الزمنية (2003- 2015) المتمثلة بــ: (الناتج المحلي الإجمالي، البطالة، التضخم) وذلك باستخدام البرنامج الإحصائي (EViews.9)، وتوصلت الدراسة إلى وجود تأثير معنوي للنفقات العامة على مؤشرات التنمية الاقتصادية المذكورة أعلاه، وأوصت الدراسة إلى أن على الجهات المسؤولة مراجعة التجارب السابقة والاستفادة العملية من نتائجها التنموية والعمل على تلافي النتائج السلبية السابقة على مؤشرات التنمية الاقتصادية المتمثلة في الناتج المحلي الإجمالي ومعدلات البطالة والتضخم.
The study aimed to show the effect of public expenditure on the economic development in Iraq during the period from 2003 to 2015. In order to achieve the objectives of study, the researcher used the descriptive analytical method to show the econometric effect of public expenditure, as an independent variable, on the economic development indicators of the time series (2003 2015) represented by “Gross Domestic Product (GDP), unemployment, inflation” using the statistical program “EViews.9”. The study found that there is a significant effect of public expenditure on the above-mentioned indicators of economic development. The study recommended that the entities in charge should review the previous experiences, benefit practically from their developmental results, and work on avoiding the effects of the previous negative results on the economic development indicators represented by “Gross Domestic Product (GDP), unemployment, inflation”.
Keywords: الاقتصاد العراقي -- التنمية الاقتصادية -- النفقات العامة -- الناتج المحلي الإجمالي -- التضخم -- البطالة